2017
DOI: 10.2134/agronj2016.07.0411
|View full text |Cite
|
Sign up to set email alerts
|

Soil Waterlogging and Nitrogen Fertilizer Management Effects on Corn and Soybean Yields

Abstract: Core Ideas Excessive soil moisture resulting from extreme precipitation events during early spring can often cause decreases in corn grain yields in the midwestern United States. Each day of waterlogging resulted in an average corn grain yield loss of 0.42 Mg ha−1 and 0.72 Mg ha−1 in 2013 and 2014, respectively. Pre‐plant N fertilizer applications of non‐coated urea; polymer coated urea, and non‐coated urea+nitrification inhibitor resulted in 19% higher yields compared to the non‐treated control in 2014. Effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 38 publications
2
72
3
2
Order By: Relevance
“…However, N fertilizer applications can increase crop grain yields and quality under soil waterlogged conditions [17][18][19]. Plant's adaptive mechanisms to waterlogging, such as adventitious root growth and root re-growth may be enhanced and accelerated by N applications [20][21][22]. Nitrogen losses due to denitrification and leaching processes under waterlogged soil conditions can cause plant N deficiency and reduce plant N use efficiency (NUE) [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, N fertilizer applications can increase crop grain yields and quality under soil waterlogged conditions [17][18][19]. Plant's adaptive mechanisms to waterlogging, such as adventitious root growth and root re-growth may be enhanced and accelerated by N applications [20][21][22]. Nitrogen losses due to denitrification and leaching processes under waterlogged soil conditions can cause plant N deficiency and reduce plant N use efficiency (NUE) [23].…”
Section: Introductionmentioning
confidence: 99%
“…If reductions in maize yield come from physiological heat stress, which occurs around 35 °C 19 , the leaf surface must be substantially warmer than the air. Temperature gradients between a canopy and surrounding air largely depend on available soil moisture, with higher canopy temperatures coinciding with drier soils [20][21][22] and limited latent cooling. Hence, when atmospheric temperature is below 35 °C, damaging canopy temperatures are likely to be reached only when soil moisture is low.…”
mentioning
confidence: 99%
“…This occurred during the latter part of grain‐fill and probably had little effect on N nutrition and grain yield. Kaur et al (2016) found that 1‐d waterlogging had little effect on corn growth, whereas flooding durations of 3 and 7 d caused reduction in corn grain yields of 21 and 36% compared with non‐flood control.…”
Section: Resultsmentioning
confidence: 94%
“…When high soil moisture conditions are imposed on poorly drained soils, corn grain yield potential and fertilizer recovery are reduced (Torbert et al, 1993; Kaur et al, 2016). Welch et al (1971) found no differences in corn grain yield response between preplant (PP) and sidedress (SD) N applications in 3 of 4 yr on poorly drained Illinois soils; however, in a year of above‐normal June rainfall, corn yields with SD‐N were greater than with PP‐N; indicating greater losses of PP‐N when climatic conditions conducive to N loss occurred.…”
mentioning
confidence: 99%